The combined use of mechanical CPR and a carry sheet to maintain quality resuscitation in out-of-hospital cardiac arrest patients during extrication and transport. (August 2015) - Lyon, Richard M.; Crawford, Anna; Crookston, Colin; Short, Steven; Clegg, Gareth R.
Abstract: Background: Quality of manual cardiopulmonary resuscitation (CPR) during extrication and transport of out-of-hospital cardiac arrest victims is known to be poor. Performing manual CPR during ambulance transport poses significant risk to the attending emergency medical services crew. We sought to use pre-hospital video recording to objectively analyse the impact of introducing mechanical CPR with an extrication sheet (Autopulse, Zoll) to an advanced, second-tier cardiac arrest response team. Methods: The study was conducted prospectively using defibrillator downloads and analysis of pre-hospital video recording to measure the quality of CPR during extrication from scene and ambulance transport of the OHCA patient. Adult patients with non-traumatic OHCA were included. The interruption to manual CPR to during extrication and to deploy the mechanical CPR device was analysed. Results: In the manual CPR group, 53 OHCA cases were analysed for quality of CPR during extrication. The median time that chest compression was interrupted to allow the patient to be carried from scene to the ambulance was 270 s (IQR 201–387 s). 119 mechanical CPR cases were analysed. The median time interruption from last manual compression to first Autopulse compression was 39 s (IQR 29–47 s). The range from last manual compression to first Autopulse compression was 14–118 s. Conclusion: Mechanical CPR used in combination with an extrication sheet can be effectively used to improve the quality of resuscitation during extrication and ambulance transport of the refractory OHCA patient. The time interval to deploy the mechanical CPR device can be shortened with regular simulation training.